Targeting COX-2/PGE2 Pathway in HIPK2 Knockdown Cancer Cells: Impact on Dendritic Cell Maturation - Garufi, Alessia; Pistritto, Giuseppa; Ceci, Claudia; Di Renzo, Livia; Santarelli, Roberta; Faggioni, Alberto; Cirone, Mara; D’Orazi, Gabriella (PLOS ONE, 2012)
Background Homeodomain-interacting protein kinase 2 (HIPK2) is a multifunctional protein that exploits its kinase activity to modulate key molecular pathways in cancer to restrain tumor growth and induce response to therapies. For instance, HIPK2 knockdown induces upregulation of oncogenic hypoxia-inducible factor-1 (HIF-1) activity leading to a constitutive hypoxic and angiogenic phenotype with increased tumor growth in vivo. HIPK2 inhibition, therefore, releases pathways leading to production of pro-inflammatory molecules such as vascular endothelial growth factor (VEGF) or prostaglandin E2 (PGE2). Tumor-produced inflammatory mediators other than promote tumour growth and vascular development may permit evasion of anti-tumour immune responses. Thus, dendritic cells (DCs) dysfunction induced by tumor-produced molecules, may allow tumor cells to escape immunosurveillance. Here we evaluated the molecular mechanism of PGE2 production after HIPK2 depletion and how to modulate it. Methodology/Principal findings We show that HIPK2 knockdown in colon cancer cells resulted in cyclooxygenase-2 (COX-2) upregulation and COX-2-derived PGE2 generation. At molecular level, COX-2 upregulation depended on HIF-1 activity. We previously reported that zinc treatment inhibits HIF-1 activity. Here, zinc supplementation to HIPK2 depleted cells inhibited HIF-1-induced COX-2 expression and PGE2/VEGF production. At translational level, while conditioned media of both siRNA control and HIPK2 depleted cells inhibited DCs maturation, conditioned media of only zinc-treated HIPK2 depleted cells efficiently restored DCs maturation, seen as the expression of co-stimulatory molecules CD80 and CD86, cytokine IL-10 release, and STAT3 phosphorylation. Conclusion/Significance These findings show that: 1) HIPK2 knockdown induced COX-2 upregulation, mostly depending on HIF-1 activity; 2) zinc treatment downregulated HIF-1-induced COX-2 and inhibited PGE2/VEGF production; and 3) zinc treatment of HIPK2 depleted cells restored DCs maturation.